2015
DOI: 10.1093/jxb/erv002
|View full text |Cite
|
Sign up to set email alerts
|

A defence-related Olea europaea β-glucosidase hydrolyses and activates oleuropein into a potent protein cross-linking agent

Abstract: Oleuropein, the major secoiridoid compound in olive, is involved in a sophisticated two-component defence system comprising a β-glucosidase enzyme that activates oleuropein into a toxic glutaraldehyde-like structure. Although oleuropein deglycosylation studies have been monitored extensively, an oleuropein β-glucosidase gene has not been characterized as yet. Here, we report the isolation of OeGLU cDNA from olive encoding a β-glucosidase belonging to the defence-related group of terpenoid-specific glucosidases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 60 publications
3
66
0
5
Order By: Relevance
“…Knowing that oleuropein aglycone exhibits strong protein-denaturing/protein-cross-linking properties (Koudounas et al, 2015), we asked whether the enzymatically produced oleuropein aglycone had any impact on the activity of the enzyme. Interestingly, no significant difference in the enzymatic activity could be observed between reactions incubated for 5, 10, or 15 min, in the presence or the absence of bovine serum albumin (BSA; i.e.…”
Section: Oeglu Kinetic Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowing that oleuropein aglycone exhibits strong protein-denaturing/protein-cross-linking properties (Koudounas et al, 2015), we asked whether the enzymatically produced oleuropein aglycone had any impact on the activity of the enzyme. Interestingly, no significant difference in the enzymatic activity could be observed between reactions incubated for 5, 10, or 15 min, in the presence or the absence of bovine serum albumin (BSA; i.e.…”
Section: Oeglu Kinetic Parametersmentioning
confidence: 99%
“…Accordingly, the OeGLU compartmentalization could allow the oleuropein/OeGLU dual-partner defense system to be inadequately active within olive cells where both OeGLU and oleuropein are highly accumulated (Amiot et al, 1986;Gutierrez-Rosales et al, 2012;Koudounas et al, 2015). In silico analysis of the OeGLU was predicted to contain a putative NLS at amino acid 542 to 550 (DRRKRLRGS) and no nuclear export signal (Supplemental Fig.…”
Section: Oeglu Is Localized In the Nucleusmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, it has been shown that iridoid toxicity can be attributed to the highly reactive aglycones that are released from the corresponding nontoxic iridoid glucosides that are often safely stored in plant organelles [18,19]. Glycoside hydrolysis can be achieved nonenzymatically or enzymatically by β-glucosidases (hydrolases, EC 3.2.1.21) produced by the plants themselves [20][21][22] or by their enemies [12,13,23,24]. If the resulting compound is a reactive aldehyde, it has the ability to link irreversibly and nonselectively essential cellular components including proteins.…”
Section: Introductionmentioning
confidence: 99%